Cell Culture and Coculture for Oncological Research in Appropriate Microenvironments. Issue 2 (5th June 2019) - Chhetri, Apekshya; Chittiboyina, Shirisha; Atrian, Farzaneh; Bai, Yunfeng; Delisi, Davide A.; Rahimi, Rahim; Garner, John; Efremov, Yuri; Park, Kinam; Talhouk, Rabih; Lelièvre, Sophie A.
Abstract: With the increase in knowledge on the importance of the tumor microenvironment, cell culture models of cancers can be adapted to better recapitulate physiologically relevant situations. Three main microenvironmental factors influence tumor phenotype: the biochemical components that stimulate cells, the fibrous molecules that influence the stiffness of the extracellular matrix, and noncancerous cells like epithelial cells, fibroblasts, endothelial cells, and immune cells. Here we present methods for the culture of carcinomas in the presence of a matrix of specific stiffness, and for the coculture of tumors and fibroblasts as well as epithelial cells in the presence of matrix. Information is provided to help with choice and assessment of the matrix support and in working with serum‐free medium. Using the example of a tissue chip recapitulating the environmental geometry of carcinomas, we also highlight the development of engineered platforms that provide exquisite control of cell culture parameters necessary in research and development. © 2019 by John Wiley & Sons, Inc.